ANALISIS SAJIAN MATERI VOLUME BANGUN RUANG PRISMA PADA BUKU TEKS MATEMATIKA KELAS V SEKOLAH DASAR BERDASARKAN PRAKSEOLOGI - Siti Nadia Herdianti, - (2023)
This research aims to comprehensively describe the characteristic of the content of mathematics textbooks for fifth grade elementary school on the concept of solid geometry volume material. This research employs a qualitative approach with a case research design. The object of this research is the mathematics textbooks of fifth-grade students and mathematics textbooks of fifth-grade teachers in Elementary School, with the subjects of this research involving both the students and teachers of fifth grade in Elementary School. The data collection techniques in this research include analyzing students' learning history documents on the topic of the volume of triangular prismatic solids, conducting interviews, and using documentation. The research findings indicate that the presentation of the topic of the volume of triangular prismatic solids in the mathematics textbook, based on praxeology, is quite satisfactory. Several sets of tasks are presented with alternative solutions. However, there are several task presentations that cause learning obstacles for the students. The findings are based on the analysis of unfulfilled elements of praxeology. The results of observing the students' learning history and conducting interviews with both the students and teachers indicate the need for improvements to supplement the presentation of the topic of the volume of triangular prismatic solids by including several solution techniques that are not well presented in both the students' mathematics textbooks and the teachers' mathematics textbooks. Furthermore, the prerequisite material is not facilitated in the students' mathematics textbooks, the space for students' activities to construct understanding related to the volume of triangular prismatic solids has not been adequately presented with complete solution techniques, thereby leaving no room for students to tackle sets of tasks with alternative solutions. Moreover, there is a lack of available didactic alternatives for solution techniques in the teachers' mathematics textbooks.